The Unseen Curriculum: Narratives of Transgender Resistance in India’s Educational Institutions - Kamath, Krishna; V. Vaidya, Sharvari (Journal of Neonatal Surgery, 2025)
Educational institutions in India, often regarded as instruments of empowerment and social mobility, simultaneously function as powerful mechanisms of regulation and exclusion for transgender and gender-diverse individuals. The everyday operations of schooling—from gender-segregated facilities and binary documentation to normative curricula and faculty apathy—are governed by an insidious hidden curriculum that reinforces cisnormativity, upholds patriarchal norms, and renders non-conforming identities invisible. The review critically examines how these institutional logics manifest within schools and universities and explores how transgender students confront, navigate, and resist them through diverse strategies of survival and subversion. Drawing on interdisciplinary frameworks from queer theory, intersectionality, and critical pedagogy, the review explores the layered nature of marginalization where caste, region, language, and class intersect with gender identity. It highlights the stark underrepresentation of vernacular, Dalit, Adivasi, rural, and non-binary experiences in dominant academic discourse, which continues to center urban, English-speaking, dominant-caste narratives. At the same time, it foregrounds the creative and political forms of resistance enacted by transgender students—through bodily autonomy, campus organizing, digital counter publics, autobiographical writing, and grassroots activism—which contest institutional erasure and assert transgender lives as sites of legitimate knowledge production. The review identifies key gaps in the existing literature, including limited empirical focus on educators, curricular content, and the absence of trans-authored scholarship. It argues for a paradigm shift from inclusion-as-access to inclusion-as-transformation—advocating for trans-affirmative educational frameworks rooted in justice, plurality, and epistemic dignity.